The effects of Section 179 deductions and bonus depreciation on farm financial investment - Hinkle, Bailey K. (Kansas State University, 2021)
The purpose of this thesis is to measure the effects of Section 179 deduction and bonus depreciation levels on investment and specific farm financial ratios. This thesis provides insight into Section 179 and bonus depreciation, key policies that have shaped these deductions as well as the use of these provisions in the state of Kansas. The study uses farm level data from the Kansas Farm Management Association (KFMA) to create a panel data set representing 518 farms, including variables for capital investment, Section 179 deductions, bonus depreciation, and multiple financial ratios. To estimate the effects, lag variables are used as independent variables in each model. The results indicate that higher Section 179 deduction use leads to a statistically significant increase in the working capital ratio, capital debt repayment capacity and owner equity percent and statistically significant decrease in the probability of default. As the use of Section 179 deduction level increases, the working capital ratio increases, the capital debt repayment capacity increases, the owner equity percent increases, and the probability of default decreases. The results are statistically significant for lagged values up to three years for Section 179 deductions for the working capital ratio, probability of default and capital debt repayment capacity and up to one year related to owner equity percent. The deduction increases the liquidity for farms, increases the ability to repay on capital investments, and decreases the probability of default for three years into the future. The deduction also increases the solvency for one year into the future. The amount of bonus depreciation and the amount of capital investment were not statistically significant in explaining the liquidity, repayment, leverage and probability of default measures.
Keywords: Section 179; Bonus depreciation; Farm financial investment; Section 179 deduction